Pengaruh Brand Image dan Brand Trust terhadap Loyalitas Nasabah Bank Kalsel Banjarmasin - Gusti Abdi Rachman; Rahmatul Jannatin Naimah; Rudy Haryanto (P3M Politeknik Negeri Banjarmasin, 2023)
This study was conducted to analyze the effect of Brand Image and Brand Trust on Customer Loyalty at PT Bank Pembangunan Daerah Kalsel in Banjarmasin City, which aims to determine brand image and brand trust partially and simultaneously customer loyalty. This research uses a purposive sampling technique with 100 PT Bank Pembangunan Daerah Kalsel customer respondents in Banjarmasin City. The analysis method used in this research is Multiple Linear Regression Analysis. The findings of this study indicate that Brand Image partially has a positive but insignificant effect, and Brand Trust partially has a positive and significant impact. While simultaneously, Brand Image and Brand Trust significantly affect customer loyalty. The value (Adjusted R Square) shows that Brand Image and Brand Trust can explain customer loyalty by 80%. In comparison, the remaining 20% is influenced by other variables besides Brand Image and Brand Image in this study. The results of this study are also customarily distributed; there are no symptoms of multicollinearity, no heteroscedasticity, no autocorrelation problems or symptoms, all x variables against y results are linear, and all variables are valid and reliable.